Nucleation kinetics of lithium phosphate precipitation. Issue 24 (1st June 2022) - Emmanuel, Michael; Papp, Paszkál; Schuszter, Gábor; Deák, Ágota; Janovák, László; Tóth, Ágota; Horváth, Dezső
Abstract : Fourth-order kinetics arises from the consecutive complexation leading to precipitation. Abstract : Lithium phosphate is an important material today in battery technology and catalysis, the source of which is gradually depleting. In this work we provide insights into the kinetics of lithium phosphate precipitation in a supersaturated solution, by monitoring the turbidity of a well-stirred reactant mixture at different concentrations and temperatures. The analysis of experimental data has revealed that nucleation can be described by a power law resembling mass action kinetics. The constructed reaction kinetic model that includes consecutive reversible complex formation preceding the heterogeneous reaction provides data which quantitatively match the experimental results, allowing detailed explanation of the mechanism of nucleation. Classical nucleation theory applied for the homogeneous nucleation of sparingly soluble salts is also consistent with the experiments.